A Carol Dickens Christmas a novel - Averill, Thomas Fox (Albuquerque, New Mexico University of New Mexico, 2014)
It's Christmas, and Carol Dickens's life is in major transition. Her son Finn, a talented trumpet player, is about to leave for college. Her ex-husband, a real-estate wheeler-dealer, wants to sell their properties in Kansas and move to Arizona. Her wheelchair-bound friend, Laurence, has fallen in love with her. To top it all off, Scraps, the family dog, is dying. As her world spins out of control, Carol seeks refuge in her research on the use of the semicolon--and in her ritual of cooking the perfect series of Victorian holiday meals inspired by A Christmas Carol.
102575
Keywords: Academic librarians; Christmas stories